Pelatihan Penulisan Ilmiah bagi Mahasiswa sebagai Strategi Penguatan Budaya Akademik di Perguruan Tinggi: id - Nur Fadillah; Iswahyudi Indra Putra; A. Muhammad Idkhan; Dennis Lorens (V-MACHINE: Vocational and Mechanical Community Service Journal, 2026)
Scientific writing skills constitute a fundamental competency representing students' critical reasoning, information literacy, and academic integrity. However, students frequently encounter technical problems, such as idea formulation, manuscript structure mastery, reference management, and adaptation to journal guidelines. To address these issues, this community service program was initiated to escalate students' manuscript writing capacities while strengthening the institutional academic climate. The methodological approach implemented involved comprehensive training and mentoring for 35 participants through the stages of needs analysis, material dissemination, writing practice, peer review, manuscript revision, and evaluation. Data collection utilized pretests, posttests, observations, scoring rubrics, and questionnaires. The program findings indicated a significant improvement in participants' comprehension, marked by a surge in the average score from 45.0 (pretest) to 78.4 (posttest), reflecting an increase of 33.4 points (74.2%). As a practical output, 28 students successfully formulated scientific article drafts, of which 16 were projected for further mentoring, and 7 were recommended for dissemination in seminar proceedings or student journals. In conclusion, practice-based educational interventions, continuous feedback, and structured mentoring proved effective in catalyzing academic competencies and the publication tradition in higher education.